The renaissance of Islam History, culture and society in the 10th century Muslim world - Mez, Adam 1869-1917 (I.B. Tauris, 2024)
The tenth century was a formative period for Islamic culture and Adam Mez's Renaissance of Islam offers a detailed survey of the Muslim world during that period. No other single work covers the subject as comprehensively. Mez drew upon a vast range of sources to produce a detailed account of all aspects of Islamic culture and society - finance, religion, geography, industry and trade, law, morals, navigation, etc. The result is a lucid and engaging work that even today remains a key resource for researchers and students alike. The original edition is now very rare. This new edition, introduced by Hugh Kennedy, one of the leading scholars of the period, makes the work available once again and includes a bibliography and index specially prepared for this edition
First published in Patna 1937
Keywords: Geschichte 900-1000; Islam; Kultur